Pengembangan Media Scrapbook pada Pembelajaran IPA Materi Gaya Dan Gerak Kelas IV SD - Alan Hidayat; Yuni Krisnawati; Dedy Firduansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop a product for developing Scrapbook Media on Natural Science Learning Materials, Materials of Style and Movement for Grade IV SD Negeri Nawangsasi in accordance with the 2013 curriculum and produce scrapbook media that are valid, practical and effective for use in learning. This research is a development research with a four-dimensional development model. Based on the results of the assessment analysis by the three experts, namely: linguists 0.75%, media experts 0.82% and material experts 0.87%, it shows that Scrapbook Media in learning science, material for style and motion, meets the high criteria. While the research results on the teacher's practicality sheet obtained an average of 89.2% and students consisting of 6 people obtained an average of 87.5% that the Scrapbook Media in learning science material on style and motion meets the very practical criteria. And the results of the research on the effectiveness of all fourth grade students obtained that Scrapbook Media in science learning on force and motion material met the High criteria with a final score of 0.74, so it can be concluded that Scrapbook Media in Science learning on force and motion material met the criteria valid, practical and effective and can be used in learning. Keywords: Natural Sciences, Scrapbook Media, 4D Development